Time scales of magmatic processes from modeling the zoning patterns of crystals - Costa, Fidel (2012)
The advent of polarized light microscopy in the middle of the 19th century allowed mineralogists and petrologists interested in igneous rocks to recognize the widespread occurrence of fine-scale heterogeneities in the optical properties of minerals (e.g., see Young 2003 for details). The interpretation of mineral zoning patterns as archives of magmatic processes has been with us for some time (e.g., Larsen et al. 1938; Tomkeieff 1939). The development of the electron microprobe in the 1960’s allowed mineral zoning profiles to be quantitatively analyzed and modeled (e.g., Bottinga et al. 1966; Moore and Evans 1967). Enhanced textural observations permitted recognition of many kinds of detailed structures during the growth and dissolution of magmatic minerals (Fig. 1⇓; e.g., Anderson 1983; Pearce and Kolisnik 1990), and these processes were also explored using experimental and numerical models (e.g., Albarède and Bottinga 1972; Lofgren 1972; Kirkpatrick et al. 1976; Loomis 1982). Major element zoning patterns are routinely measured, and with the arrival of the ion microprobe, the identification of heterogeneous distribution of trace elements opened the window for more realistic and sophisticated scenarios and models (Fig. 1⇓; e.g., Kohn et al. 1989; Blundy and Shimizu 1991; Singer et al. 1995). We now measure abundances of naturally occurring isotopes at the scale of tens of micrometers (e.g., Davidson et al. 2007a; Ramos and Tepley 2008) and this allows in situ dating of crystals (e.g., Cooper and Reid 2008).